Prolonged In Vitro Exposure to Methylmalonic Acid Induces Inflammation, Glutamate Metabolism Disruption, and Alters Functional Gene Expression in C6 Astroglial Cells - Rômulo Rodrigo de Souza Almeida; Larissa Daniele Bobermin; Izaviany Schmitz; Filipe Renato Pereira Dias; Caio César Ramalho Bezerra; Mariana Rocke-Peters; Ester Rezena; Krista Minéia Wartchow; Fernanda Urruth Fontella; Diogo Onofre Souza; Moacir Wajner; Carlos-Alberto Gonçalves; et al. (Neurotoxicity Research, 2026)
Methylmalonic acidemia is an inherited neurometabolic disorder characterized by accumulation of methylmalonic acid (MMA) in different tissues, particularly in the brain. As a result, patients frequently exhibit progressive neurological deterioration, accompanied by episodes of acute encephalopathy following metabolic decompensation. Astrocytes are glial cells that maintain the central nervous system homeostasis and may be important cellular targets of MMA-induced dysfunction. However, most in vitro experimental models for the study of methylmalonic acidemia are based on short-term exposure to the toxic metabolites that accumulate in patients. In this study, we used a prolonged experimental model, which has not been yet explored in the context of glial cells, focusing on the inflammatory response, glutamate metabolism, and putative signaling pathways that can contribute to understanding cellular damage observed in methylmalonic acidemia. It is emphasized that MMA is persistently elevated in the brain of the affected patients. Prolonged MMA exposure induced inflammation with significant increase in gene expression of cyclooxygenase 2, interleukin (IL)-1β and its receptor (IL1R1), and IL-6, accompanied by a decrease in IL-10 expression. MMA also increased glutamate uptake and the activity and gene expression of the enzyme glutamine synthetase, while it downregulated glial cell-derived neurotrophic factor (GDNF). The expression of NFκB, p38 MAPK, Nrf2, heme oxygenase 1, PGC-1α, and sirtuin 1 were also modulated by MMA treatment, indicating the critical role of these signaling pathways in the MMA-induced persistent gliotoxicity. Finally, it is conceivable that these changes may significantly contribute to clarify the pathogenesis of methylmalonic acidemia.